Leveraging Developing Economies With the Use of Information Technology 2012
DOI: 10.4018/978-1-4666-1637-0.ch007
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of National IT Policies, Socio-economic Factors, and National Culture on Network Readiness in Africa

Abstract: This study examines the influence of national IT policies, socio-economic and cultural factors on the network readiness of African countries. The capability and level of preparation of a nation to participate in and benefit from information and communication technologies (ICT) for socio-development is assessed by the network readiness index. Prior studies have shown that such factors have a significant influence on how a country benefits from its use of ICT products for development. Research on this topic with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This result is partly consistent with a study of [42], which found that some socio-demographic characteristics such as age and sex showed significance in the adoption of broadband in a local community (the London Borough of Hillingdon) in the UK, while the characteristics such as education and income did show significance in the same context. Similarly, [43] showed significance between some of the socioeconomic factors (e.g. education and economic wealth) and the ability of African regions to leverage ICT products and services for development and growth.…”
Section: Resultsmentioning
confidence: 99%
“…This result is partly consistent with a study of [42], which found that some socio-demographic characteristics such as age and sex showed significance in the adoption of broadband in a local community (the London Borough of Hillingdon) in the UK, while the characteristics such as education and income did show significance in the same context. Similarly, [43] showed significance between some of the socioeconomic factors (e.g. education and economic wealth) and the ability of African regions to leverage ICT products and services for development and growth.…”
Section: Resultsmentioning
confidence: 99%